Exploiting bi-stable magneto-piezoelastic absorber for simultaneous energy harvesting and vibration mitigation. (1st October 2021) - Rezaei, Masoud; Talebitooti, Roohollah; Liao, Wei-Hsin
Highlights: Efficient energy harvesting and vibration suppression by a bi-stable absorber is investigated. Nonlinear magneto-electromechanical model is obtained via the Hamilton's principle. Steady-state vibrations are effectively mitigated via strongly modulated response. When vibration suppression and energy harvesting are of the same importance, the bistable absorber performance is 46.5% better than a linear absorber. When energy harvesting has priority, the proposed absorber performance is 158 % higher than a linear absorber. Abstract: This paper investigates efficient simultaneous energy harvesting and vibration suppression utilizing a tunable bi-stable magneto-pieozelastic absorber (BMPA). The absorber comprises a bimorph cantilever beam exposed to a magnetic field. Furthermore, it is attached to a primary simply supported beam which is under an external excitation. The nonlinear magneto-electromechanical equations governing the coupled continuous system are derived utilizing the Hamilton's principle. First, the nonlinear magnetic force and its bifurcations are explored. Next, using numerical approaches, the efficacy of the absorber under a transient excitation from energy harnessing and vibration annihilation viewpoints is assessed. Furthermore, the efficiency of the BMPA in a steady-state harmonic excitation is investigated, both in time and frequency domains. Bifurcation diagrams disclosed that, based on magnets gap, the absorber performs periodic in-well low-amplitude oscillations, chaotic inter-well large-amplitude vibrations, or periodic high-amplitude motions. However, it is observed that in inter-well oscillations, chaotic strongly modulated response occurs and efficiency of the BMPA in vibration mitigation and energy harvesting markedly improves, compared to a linear absorber. Moreover, perfection rate examinations disclosed that when vibration suppression and energy harvesting are of the same importance, the bistable PZT absorber performance is 46.5% better than the corresponding linear absorber. Furthermore, when energy harvesting has priority, the BMPA performance is 158% higher than the linear absorber. Finally, harmonic balance method along with pseudo-arclength scheme are exploited to investigate the efficacy in large-amplitude inter-well scenario. It is illustrated that the system solutions are nonlinear and experience various cyclic fold and Hopf bifurcations. Further, the frequency response curves revealed that the BMPA decreases the host structure vibrations. Moreover, in this scenario, a considerable level of voltage is generated over a wide frequency range. Graphical abstract: Image, graphical abstract